Salvage total hip arthroplasty after two gamma 3 nail failures: a case report - Stepanovic, Z. L; Ristic, B. M (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2015)
We report a case of 68-year-old female patient who suffered two Gamma 3 nail breakages following trochanteric fixation failure revision surgery. A patient was primarily treated with sliding hip screw. Revision surgeries of reverse trochanteric nonunion were performed with short Gamma 3 nails and bone grafting. The nail failures occurred 11 and 7 months after implantation. This undesired series of events were caused by inappropriate implant selection, thus replacing the nail to a modular total hip arthroplasty was more effective as salvage surgery. Key words: salvage total hip arthroplasty, gamma nail, sliding hip screw, fixation failure, reverse trochanteric fracture, nonunion.
Keywords: Bone Screws; fraktury kyčle; Aged; Fracture Fixation, Intramedullary; senioři; Salvage Therapy; lidé; intramedulární fixace fraktury; Treatment Failure; Arthroplasty, Replacement, Hip; Bone Nails; reoperace; Female; neúspěšná terapie; Reoperation; ženské pohlaví; Humans; kostní šrouby; záchranná terapie; kostní hřeby; náhrada kyčelního kloubu; Hip Fractures